Trade like Jesse Livemore - Smitten, Richard (John Wiley & Sons, 2005)
author Richard Smitten explores the technical aspects of Livermore’s trading approach and shows readers how they can use these techniques to garner the success Livermore once did. Trade Like Jesse Livermore covers every aspect of Livermore’s trading methods, from discerning market behavior and trends such as top-down and tandem trading to paying close attention to indicators such as one-day reversals and spikes. With this book as their guide, readers can learn how to trade profitably without fear or greed.